PERUBAHAN KADAR AIR UBI KAYU SELAMA PENGERINGAN MENGGUNAKAN PENGERING KABINET - Ardianto, Ardianto; Jamaluddin P, Jamaluddin P; Wijaya, Mohammad (Universitas Negeri Makassar, 2017)
This research aims to find out the changes in cassava water content during the drying process with drying cabinet. Drying cassava is done at temperature from 40OC to 60OC with various length of drying from 2 hours to 6 hours. During the drying process, the changes in water content of the sample were obseved at various temperatures and drying lengths. The resulth research shows that there are changes in cassava water content which is dried using drying cabinet at various temperatures and drying lengths. The longer the time and the higher the drying temperature, the quicker the decrease of water content in the dried cassava sample based on statistic analysis using IBM SPSS 2.1 version, it is described that the best drying process is obtained at 60OC drying temperature an 2 hours drying length